Identification of the parent bodies of micrometeorites from the Wideroefjellet, Sør Rondane Mountains, by means of oxygen isotopes - Matthias, Van Ginneken; Steven, Goderis; Bastien, Soens; Vinciane, Debaille; Janaina, Avila; Peter, Holden; Seann, McKibbin; Philippe, Claeys; Trevor, Ireland (2017)
第8回極域科学シンポジウム/個別セッション：[OA] 南極隕石 12月6日（水）国語研究所 2階講堂 The Eighth Symposium on Polar Science/Ordinary sessions: [OA] Antarctic meteorites Wed. 6 Dec./2F Auditorium, National Institute for Japanese Language and Linguistics conference object